Mise en évidence d’une fosse à fumure du Haut-Empire au Pont-Chrétien-Chabenet (Indre) - Sandrine Bartholome; Morgane Liard (Revue Archéologique du Centre de la France)
It is within the work of an archaeological diagnosis carried out on the commune of the Pont-Chrétien-Chabenet, Indre, that a manure pit was discovered. It was related to an agrarian settlement, dated between the 1st and 3d centuries AD. Such specific structures from pars rustica of ancient villae are directly related to the need for amendment of cultivated land. They are still poorly studied, for being rarely identified. In recent years, interest in the ancient rural economy and especially in the functional organization of the settlements allows to question about these structures closely linked to an essential practice of the Roman agricultural economy. Their locations and morphologies are now better known even if these structures remain difficult to apprehend. In the Centre-Val de Loire region, the corpus, including five Roman rural settlements (one in Indre-et-Loire, one in Eure-et-Loir, two in Loir-et-Cher and one in Loiret), is now completed by this new discovery in the Indre. This contribution adds, to this still limited set, the first manure pit identified in Indre, whose functioning is dated between the second half of the 2nd and the 3nd centuries AD.